ANALISIS GEOMETRI JALAN ANGKUT TAMBANG PADA PT. NATURAL PERSADA MANDIRI KECAMATAN LASOLO KEPULAUAN KABUPATEN KONAWE UTARA PROVINSI SULAWESI TENGGARA - Erwin; Kasmira; Zulfahmi; Gina Audina P Alhabsyi (Journal Teknik Dan Teknologi, 2025)
The purpose of this study is to Analysis of the geometry of the mine haul road at PT. Natural Persada Mandiri, especially in the Bumi Pit 7 Block to the stockpile based on the mine haul road recommendation that refers to the AASTHO standard, which is located in Waturambaha, Lasolo Islands District, Konawe Utara Regency, Southeast Sulawesi Province in the IUP (Mining Business Permit) area of PT. Binanga Hartama Raya. Based on the design results of the mine haul road using Surpac 6.3, the road from Blok Bumi Pit 7 to the stockpile has a track length of ± 610 meters referring to the recommendation of the mining road geometry where the straight road width is 9 meters, the road width at the bend is 11 meters, 4% super elevation, slope the length of the road ranges from 8% - 10%. Because the new land clearing will be held, the researchers designed a road that is in accordance with existing safety standards, thus obtaining safe results for the Hino 500 FM 260 JD transportation means.